Chi impara da chi? Fare antropologia con la scuola tra ricerca e azione - Lofranco, Zaira T.; Ginesi, Virginia; Reinini, Maria Luigia (Antropologia Pubblica, 2019)
In the last two years ago Italian schools have been considered a crucial are-na where to bring anthropology into. Nonetheless, this study suggests that the value of anthropology in the public sphere and in education settings could be better acknowledged if we show what anthropologists and other school professionals can achieve working to-gether. In this perspective, this contribution gives an account of the collaboration among an anthropologist, a headmaster and a teacher. The focus is the elaboration of a shared meaning of their mission through researching, planning and implementing intercultural activities in a public school in the Italian province of Bergamo.Framing their activities in a cooperative learning approach, where the teaching and learning roles are shared, the authors demonstrate how working with both cultural and professional diversity in schools can re-shape the whole educational project.